Violation of the Code of Ethics for Constitutional Judges in the Constitutional Court's Decision on Requirements for Presidential and Vice Presidential Candidates - Pirdaus, Dede Irman; Sidiq, Fahmi; Rusyn, Volodymyr (International Journal of Humanities, Law, and Politics, 2024)
As a country based on legal principles, Indonesia has a responsibility to respect and prioritize the principles of the rule of law, including independence and the absence of partiality in the judicial system. The level of success in implementing this principle can be measured by the extent to which the judiciary is independent in carrying it out to realize justice based on the law. However, the power of the Constitutional Court (MK) cannot be avoided from criticism and evaluation. For example, a Constitutional Court decision attracted public attention regarding the requirements for presidential and vice presidential candidates. Therefore, this article discusses the impact of the controversy that emerged after the decision of the Constitutional Court (MK) in Case Number 90/PUU-XXI/2023 on January 4 2023. This decision, which includes the cancellation of part of Law Number 7 of 2017, has raised various criticisms and doubts about the independence of the Constitutional Court. By focusing on the role of Chief Justice of the Constitutional Court Anwar Usman in minority opinions, this article analyzes the examination carried out by the Honorary Council of Constitutional Court Judges (MKMK) regarding alleged ethical violations. The implications for the credibility of the Constitutional Court as a democratic oversight institution are a major concern in this context.